2018
DOI: 10.1088/1748-9326/aab650
|View full text |Cite
|
Sign up to set email alerts
|

What is the potential of cropland albedo management in the fight against global warming? A case study based on the use of cover crops

Abstract: Land cover management in agricultural areas is a powerful tool that could play a role in the mitigation of climate change and the counterbalance of global warming. First, we attempted to quantify the radiative forcing that would increase the surface albedo of croplands in Europe following the inclusion of cover crops during the fallow period. This is possible since the albedo of bare soil in many areas of Europe is lower than the albedo of vegetation. By using satellite data, we demonstrated that the introduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 32 publications
2
80
2
Order By: Relevance
“…However, because of the diverse nature of Earth system feedback 42 , accounting for it through an adjustment in CO 2 emissions is not always straightforward. For example, if a feedback system results in the release of other greenhouse gases or affects the Earth system through changes in surface albedo, clouds or fire regimes, for example, its contribution needs to be translated into an equivalent CO 2 correction term (see refs 89,90 for example). Because most Earth system feedback is either sensitive to rising CO 2 or to variations in climate parameters, it is expected that these contributions are scenario-dependent, nonlinear, and in some cases realized over longer timescales only 40,41,85,[91][92][93][94][95][96][97][98] .…”
Section: Perspective Researchmentioning
confidence: 99%
“…However, because of the diverse nature of Earth system feedback 42 , accounting for it through an adjustment in CO 2 emissions is not always straightforward. For example, if a feedback system results in the release of other greenhouse gases or affects the Earth system through changes in surface albedo, clouds or fire regimes, for example, its contribution needs to be translated into an equivalent CO 2 correction term (see refs 89,90 for example). Because most Earth system feedback is either sensitive to rising CO 2 or to variations in climate parameters, it is expected that these contributions are scenario-dependent, nonlinear, and in some cases realized over longer timescales only 40,41,85,[91][92][93][94][95][96][97][98] .…”
Section: Perspective Researchmentioning
confidence: 99%
“…Two simple empirical parameterizations of shortwave radiative transfer have been widely applied within the LULCC science community for estimating F from α s (Bozzi et al, 2015;Caiazzo et al, 2014;Carrer et al, 2018;Cherubini et al, 2012;Muñoz et al, 2010). While these parameterizations are also based on a single-layer atmosphere model of shortwave radiative transfer, at the core of these parameterizations is the fundamental assumption that radiative transfer is wholly independent of (or unaffected by) α s .…”
Section: Simple Empirical Parameterizations Of the Lulcc Science Commmentioning
confidence: 99%
“…Within the LULCC science community, two methods have primarily met the need for efficient F calculations from α s : simplified parameterizations of atmospheric transfer of shortwave radiation (Bozzi et al, 2015;Bright and Kvalevåg, 2013;Caiazzo et al, 2014;Carrer et al, 2018;Cherubini et al, 2012;Muñoz et al, 2010) and radiative kernels (Ghimire et al, 2014;O'Halloran et al, 2012;Vanderhoof et al, 2013) derived from sophisticated radiative transfer schemes embedded in GCMs (Block and Mauritsen, 2014;Pendergrass et al, 2018;Shell et al, 2008;Soden et al, 2008). Simplified parameterizations of the LULCC science community have not been evaluated comprehensively in space and time.…”
Section: Introductionmentioning
confidence: 99%
“…Like in Arctic by a tundra-to-shrubland or a tundra-to-forest transition (Eugster et al, 2000;Souther et al, 2014); the South American Chaco (Houspanossian et al, 2017), in the tropical rain forests, and the Swiss Alps mountains in Europe (Rangwala and Miller, 2012), land cover change must be change the absorption active of sunlight. Especially for the human-induced land use changes, such as in forest-cropland and grassland conversion (Carrer et al, 2018;Zhao et al, 2017). Additionally, our result all confirmed that the significant negative correlation between them, such as the slope was 0.012 (p = 0.008) for MDW, was -0.013 (p = 0.047) for DRT and was -0.010 (p = 0.031) for SHB, was -0.006, (p=0.046) for TPL (Fig.…”
Section: Fig6 the Line Regression Of Average Annual Albedo And Et Rmentioning
confidence: 99%